Conversations on Critical Thinking: Can Critical Thinking Find Its Way Forward as the Skill Set and Mindset of the Century? - Maura Sellars; Razia Fakirmohammad; Linh Bui; John Fishetti; Sarfaroz Niyozov; Ruth Reynolds; Nisha Thapliyal; Yu-Li; Nosheen Ali (MDPI AG, 2018)
The capacity to successfully, positively engage with the cognitive capacities of critical thinking has become the benchmark of employability for many diverse industries across the globe and is considered critical for the development of informed, decisive global citizenship. Despite this, education systems in several countries have developed policies and practices that limit the opportunities for students to authentically participate in the discussions, debates, and evaluative thinking that serve to develop the skill set and mindset of critical thinkers. This writing examines the status of critical thinking in four different contexts across the globe as reflected in educational policies and academic experiences as a preface to investigating actual classroom practices and possible impacts the support of critical thinking skills may have on the potential development of the global citizens of the future. Each vignette reflects the contextualized difficulties that are presented by social and cultural concerns and traditions of making meaning. These stories of education also illustrate the various ways in which the skills and capacities of critical thinking are interpreted in different contexts and address the negative nuances with which thinking critically has become associated. Finally, a pedagogical model of teaching, which may support student development of the skill set of critical thinking within the boundaries of social and cultural mindsets, has been developed.